First characterization of somatic proteins of trematodes of the family Paramphistomidae by SDS-PAGE isolated from cattle from the Cajamarca region, Peru. - Fernandez Mendoza, Charito Jennyfer (2024)
Paramphistomosis is a gastrointestinal parasitic disease with high prevalence in tropical and subtropical areas. This study characterized somatic proteins of adult trematodes of the Paramphistomidae family by SDS-PAGE. 630 adult parasites were collected from the rumen and reticulum of slaughtered cattle in Cajamarca, Peru. 21 protein bands with molecular weights ranging from 15 kDa to 119 kDa were identified. These findings may contribute to alternative control programs, including the development of vaccines and selection of appropriate drugs.